Manfaat Terapi Plasma Konvalesen pada Infeksi Covid-19 - Asep Sukohar; Zihan Zetira (Medula, 2020)
The pandemic of coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has attracted the world’s attention. On June the cases spreaded more than 200 countries and territories. America occupied the highest level of confirmed cases 4.437.946 and fatality cases 119.761. In Indonesia has 47.898 confirmed cases and 2.535 fatality cases. Until now there are no specific drugs or vaccines available to treat COVID-19. The principle therapy in Indonesia are oxygen supplementation, fluid theraphy, vasopressor drugs, empiric antibiotic, symptomatic therapy, and systemic corticosteroid. The Food and Drug Administration (FDA) recommends therapy in patients COVID-19 are use convalescent plasma taken from patients who recovered from infection. Convalescent plasma therapy is the administration of passive polyclonal antibodies (Ab) to provide immediate immunity that has been used more than a century ago. Several studies have reported that the use of convalescent plasma increases patient survival, improves clinical symptoms, decreases mortality and there are no significant adverse effects.